KAJIAN LITERATUR: KESIAPAN GURU DALAM MENGIMPLEMENTASIKAN PEMBELAJARAN IPA DENGAN PENDEKATAN FENOMENA ALAM DI SEKOLAH DASAR - Shofi Shalsabila; Deny Apriyani Juhri (Bagimu Negeri, 2025)
Teachers' readiness to implement science learning using the natural phenomena approach in elementary schools is crucial for creating effective and appropriate learning experiences. This method focuses on students' direct experiences with real-life events, making it crucial for teachers to possess the appropriate knowledge, skills, and attitudes. However, some teachers experience various challenges such as a lack of resources, training, and understanding of this approach. This study aims to identify factors influencing teacher readiness and provide suggestions for training and facilitation strategies. The results demonstrate the importance of developing practical skills for teachers so that natural phenomena-based science learning can significantly improve student creativity, motivation, and learning outcomes.